MUSEO ITINERANTE DE LA MADERA E.M.M. - Kwan, Kenny (2015)
In response to the need of the Costa Rican Institute of Wood (ICOMADERA) to develop an architectural proposal to promote the use of wood in diverse areas, it is proposed and designed a traveling structure that functions both as a museum and school, focused on education, difussion and promotion of the use of wood. Thanks to its easy installation, the project is distinguished by its adaptability to different national settings.